Ace-Pong / Siti Suraya Ashar ... [et al.] - Ashar, Siti Suraya; Ramli, Nurfaziera Dania; Madang, Sonnia Sedang; Abd Rahim, Aqillah Humaira (2021)
Ace-Pong is an ice cream and it is also a very unique dessert. Our company called Ace-Stick has been selling dessert products that are suitable for all ages. Ace-Pong Ice-cream uses a natural ingredient called Gula Apong which can be found in Sarawak. Apong sugar is a type of sugar that is very difficult to find. This Ace-Pong can be found at No 47, Jalan Cengkerik 1, Pusat Perdagangan Kempas, 81200 Johor Bahru, Johor. This is because the place is very strategic to attract customers. This is because Ace-Stick Sdn Bhd is very close to the location of residential areas and industry. Our target is to focus on the population in the surrounding area. The price of Ace-Pong is also very affordable which is RM3 (per stick) Original and RM5 (per stick) for both Golden and Silver. Ace-Pong Ice-cream has only one types of flavour which is Apong sugar. Even though it has one flavour only which is Apong sugar flavour, the customers allowed to create various add-ons to suit customers' tastes. Our company deliver our product through selling and delivery. Ace-Stick Sdn Bhd also makes services such as delivery by using Food Panda to send orders to customers who want to buy Ace-Pong Icecream. Not only that, Ace-Stick uses platforms such as using social media, promotions, business cards and even flyers to encourage people to buy our Ace-Pong Ice-cream.